2013
DOI: 10.17221/10/2012-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of adopting organic farming practices: a case study in the Czech Republic

Abstract: Th e presented article focuses on an analysis of the phenomena appearing in the implementation of the transition from classic conventional technology in the production of agricultural food products to an ecological manner of farming. Th e main objective is an empirical analysis of the determinants of the implementation of ecological production technology, whereby not only is their defi nition focused on, but also the quantifi cation of the level of their eff ect. Th e primary methodological tool for achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 22 publications
(31 reference statements)
0
26
2
3
Order By: Relevance
“…• Farm specialisation and type of farming: The effect of a high level of specialisation has been analysed particularly in NE and SE. Here, a trend perspective allows us to give a good explanation of the opposite results provided by the literature: taking into account that, in several cases, the adoption of EFFPs implies a farm diversification [112], early EFFP adopters are generally mixed farms [14,75,99,103,111,113,114], while late adopters are more specialised [74,[106][107][108]115]. Both in NE and in SE, a specialisation in permanent crops positively affects the adoption of EFFPs [45,114,[116][117][118], while the effect of specialisation in livestock differs between SE farms, where the effect is positive [14,99,[106][107][108]111,114,[117][118][119][120], and NE farms, where the effect is negative [93,103,113].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…• Farm specialisation and type of farming: The effect of a high level of specialisation has been analysed particularly in NE and SE. Here, a trend perspective allows us to give a good explanation of the opposite results provided by the literature: taking into account that, in several cases, the adoption of EFFPs implies a farm diversification [112], early EFFP adopters are generally mixed farms [14,75,99,103,111,113,114], while late adopters are more specialised [74,[106][107][108]115]. Both in NE and in SE, a specialisation in permanent crops positively affects the adoption of EFFPs [45,114,[116][117][118], while the effect of specialisation in livestock differs between SE farms, where the effect is positive [14,99,[106][107][108]111,114,[117][118][119][120], and NE farms, where the effect is negative [93,103,113].…”
mentioning
confidence: 99%
“…In AF, and especially for soil and water conservation practices [12,[66][67][68][69][70], this positive role is often linked to higher flexibility in terms of decision-making, greater access to resources, and more opportunities to test new practices on small sample plots [71,72]. In NE and SE, however, a negative effect is found in some cases, related to the higher profit-orientation of larger farms compared with smaller ones, or to the ease of management of smaller farms in the case of labour-intensive EFFPs [7,46,[73][74][75][76][77].…”
mentioning
confidence: 99%
“…Ekologické zemědělství je jedním z nejrychleji se rozvíjejících sektorů české zemědělské produkce (Malá a Malý, 2013) a rovněž český trh biopotravin vykazuje značné meziroční nárůsty (Doležalová, Pícha and Navrátil, 2009), vzory spotřebitelského chování vůči produktům ekologického zemědělství se pak vyvíjejí obdobně jako v západoevropských zemích (Zagata, 2012). Ekologicky hospodařící podniky vykazují spíše lepší hospodářskou výkonnost než podniky hospodařící konvenčním způsobem (Brožová, 2011), avšak zásadním aspektem tohoto faktu je role finanční podpory (Hrabalová a Zander, 2006, Brožová, 2011.…”
Section: Ekologické Zemědělství V čEské Republiceunclassified
“…Despite growing market and positive evolution in pricing policy of organic producers, existing literature and empirical research shows that organic producers have insufficient access to financial funds, especially in the domain of certification, organic production, research and the purchase of necessary equipment. For example, research conducted by Mala and Maly showed that some of the implementation of the organic production technology is negatively affected primarily by the rising age of farmers and that large farms do not have a tendency to make the transition to the organic production [6,18]. Besides that, limited credit mechanisms and insufficient capacity of commercial banks represent the most significant problems in the field of financing this production in Africa [7].…”
Section: Introductionmentioning
confidence: 99%